2012
DOI: 10.1371/journal.pone.0039522
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids Play a Positive Role in the Degradation of Heterocycles by Sphingobium yanoikuyae

Abstract: BackgroundMicrobial oxidative degradation is a potential way of removing pollutants such as heterocycles from the environment. During this process, reactive oxygen species or other oxidants are inevitably produced, and may cause damage to DNA, proteins, and membranes, thereby decreasing the degradation rate. Carotenoids can serve as membrane-integrated antioxidants, protecting cells from oxidative stress.FindingsSeveral genes involved in the carotenoid biosynthetic pathway were cloned and characterized from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…strain N81106 (previously Agrobacterium aurantiacum ) [ 33 ], Bradyrhizobium sp. ORS278 [ 34 ] and Sphingobium yanoikuyae XLDN2-5 [ 22 ]. Overlapping of crt ORFs is likely to facilitate coordinated gene expression, and it has been shown that the preceding ORFs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…strain N81106 (previously Agrobacterium aurantiacum ) [ 33 ], Bradyrhizobium sp. ORS278 [ 34 ] and Sphingobium yanoikuyae XLDN2-5 [ 22 ]. Overlapping of crt ORFs is likely to facilitate coordinated gene expression, and it has been shown that the preceding ORFs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, light was found to strongly affect carotenoid synthesis by all of these strains. In nonphotosynthetic bacteria, carotenoids play an important role as protectants against photo-oxidative damages (Liu et al, 2012). Carotenogenesis in these microorganisms may occur in three manners including constitutive, light-induced, or cryptic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of carotenoids produced by the genus Arthrobacter has not been distinctly revealed, one function of carotenoids in microorganisms is to serve as membrane integrated antioxidants, protecting cells from oxidative stress (Krinsky, 1989;Liu et al, 2012).…”
Section: Carotenoidsmentioning
confidence: 99%
“…nov., A. agilis, A. hyalinus) (Fong, Burgess, & Barrow, 2001;Kojima et al, 1993;Reddy et al, 2000). The nature of these compounds is still partly unknown, although some literature reported that yellow pigments belonging to the carotenoid family play an important role in physiological and molecular processes of these microorganisms such as: photosynthesis, survival to oxidative damage and resistance to UV-radiations (Dieser, Greenwood, & Foreman, 2010;Fong et al, 2001;Liu, Gai, Tao, Tang, & Xu, 2012).…”
Section: Introductionmentioning
confidence: 99%